Achalasia: an unusual cause of airway obstruction. Issue 2 (22nd January 2009) - Bruijns, S R; Hicks, A
Abstract : Achalasia is a disorder of the lower oesophageal sphincter and the smooth musculature of the oesophageal body. Although oesophageal obstruction is common, concurrent airway obstruction is exceptional. A case is presented of a 79-year-old woman admitted to the emergency department requiring intubation following out-of-hospital airway obstruction and subsequent respiratory arrest.